A peek behind the curtain in the diagnosis and management of COVID‑19‑Associated Mucormycosis (CAM) - Nermin A. Osman; Mohammed Moustapha Anwar; Bivek Singh; Girish K. Gupta; Amgad M. Rabie (SpringerOpen, 2023)
Abstract Coronavirus disease 2019 (COVID-19)-associated mucormycosis (CAM) is responsible for a high mortality rate due to its unique and severe host-pathogen interactions. Critically ill or immunocompromised COVID-19 patients are more prone to suffer from aggressive mycoses. Probable victims include those with uncontrolled diabetes mellitus (DM), metabolic acidosis, prolonged neutropenia, increased ferritin levels, hypoxia, and prolonged hospitalization with/without mechanical ventilators and corticosteroids administration. The current review aims to outline the journey of patients with CAM as well as the advantages and disadvantages of the currently available diagnostic techniques. It also discussed the current status of treatment options and caveats in the management of mucormycosis. Multidisciplinary team, early diagnosis, controlling the predisposing condition(s), complete surgical debridement, effective antifungal therapies (e.g., amphotericin B, isavuconazole, and posaconazole), and implementing antifungal stewardship programs are imperative in CAM cases.